Developing Nanodisc-ID for label-free characterizations of membrane proteins - Bao, Huan (Commun Biol, 2021)
Membrane proteins (MPs) influence all aspects of life, such as tumorigenesis, immune response, and neural transmission. However, characterization of MPs is challenging, as it often needs highly specialized techniques inaccessible to many labs. We herein introduce nanodisc-ID that enables quantitative analysis of membrane proteins using a gel electrophoresis readout. By leveraging the power of nanodiscs and proximity labeling, nanodisc-ID serves both as scaffolds for encasing biochemical reactions and as sensitive reagents for detecting membrane protein-lipid and protein-protein interactions. We demonstrate this label-free and low-cost tool by characterizing a wide range of integral and peripheral membrane proteins from prokaryotes and eukaryotes.